The gifts and challenges of anno domini - Goa, David J. (Material religion, 2012)
The year 2000 marked the beginning of the third millennium of Christian culture. It was an opportune moment to reflect on Jesus and his teaching and what has been made of them over the last 2,000 years, to ask what Christian culture has bequeathed to Western civilization, what images of Jesus were pulled forward in particular cultural epochs as part of the shaping and reshaping of ideas, art, devotion, law, politics and social relationship. Anno Domini, Jesus through the centuries was the only exhibition in a public museum in North America reflecting on the person and teaching of Jesus from whom we date our calendar. Anno Domini brought together artistic works, poetry, and song to invite the visitor to reflect and discuss a range of themes touching on meaning and purpose and on how we live together. Why was Anno Domini the only such exhibition in the year 2000? What are the sources of resistance to a consideration of this key figure in Western and world culture? How was it possible for a relatively small provincial museum in Western Canada to engage such a large and compelling set of ideas? How did the public engage the theme? What were the challenges to doing an exhibition on such a central religious and cultural theme? Where did the controversies arise and how is knowledge the single most important factor in addressing and setting them to rest?